Diagnostic Capacity for Fungal Infections in Tertiary Hospitals in Nigeria and Ghana - An Onsite Baseline Audit of 9 Sites - Damilola Akinlawon; Iriagbonse Osaigbovo; Mohammed Yahaya; Olufunmilola Makanjuola; Ubong A. Udoh; Philip Nwajiobi-Princewill; Ifeyinwa Nwafia; Jonah Peter; Isabella Asamoah; Folake Peters; Obiora Okafor; Tochi Okwor; et al. (Frontiers Media S.A., 2024)
ObjectivesTo assess diagnostic mycology capacity and available fungal diagnostic services of microbiology laboratories in eight tertiary hospitals in Nigeria and one in Ghana.MethodsOn-site audits were performed in the microbiology laboratories of nine tertiary hospitals using a structured observation checklist.ResultsA total of nine tertiary hospitals' laboratories in Nigeria and Ghana were assessed between June 2022 and December 2023. The majority of audited laboratories lacked basic infrastructure and materials needed for fungal diagnostic testing, with less than half of the labs having a dedicated mycology bench, space or room, 3/9 (33.3%), appropriate bench workflow 1/9 (11.1%), functional biosafety cabinet type two 2/9 (22.2%), dedicated incubators 3/9 (33.3%), standard operating procedures 1/9 (11.1%), mycology atlases 2/9 (22.2%). Trained laboratory personnel for mycology were also lacking with only one of the laboratories 1/9 (11.1%) observed to have a designated trained personnel for the mycology bench.ConclusionThe audit revealed deficits in basic infrastructure, material resources, dedicated human resources, and laboratory capacity to detect serious fungal infections.